Produtividade de alface cv Lucy Brown influenciada por períodos de convivência com plantas infestantes e potencial alelopático da tiririca - Melhoranca Filho, Andre Luiz [UNESP]; Rocha Pereira, Maria Renata [UNESP]; Martins, Dagoberto [UNESP]; Castro, Rodrigo Martinez [UNESP]; Nascimento, Martha Santana [UNESP] (Universidade Federal de Uberlândia (UFU), 2008)
This work was divided in two experiments, the first one to evaluate the lettuce productivity (cv Lucy Brown - American group) influenced by increasing and decreasing periods of coexisting with harmful plants, and a second moment, aiming at to evaluate the allelopathic potential of nutsedge (Cyperus rotundus L.) on the initial lettuce development.The experimental treatments constituted of six increasing and decreasing periods of coexisting with harmful plants, or control of it in the culture, considered from the plantation of the lettuce; being separate in two groups: Weeds and Clean weeds.In the second moment of the experiment, purple nutsedge aerial parts had been collected in the area of experiment 1, that drying had been after triturated and immersed in methylic alcohol P. A in ratios 10, 5,0 and 2.5% (w/ v) and later impregnated in germination paper, where had been placed lettuce seeds.The analyses of results, one concludes that the presence of C. rotundus plants can intervene with the germination, growth and development of the plants of lettuce cv Lucy Brown, and that initial periods of coexisting between the culture and the harmful are associate to an induction of the foliar area development, and can not express the reduction of productivity in the end of the cycle. Drawn out periods of competition induce the reduction of the lettuce foliar area, and then they will intervene with the yield productivity.

Este trabalho foi dividido em dois experimentos, sendo o primeiro de avaliação da produtividade de alface (cv Lucy Brown - grupo americana) influenciada por períodos crescentes e decrescentes de convivência com plantas daninhas, e um segundo, visando avaliar o potencial alelopático de tiririca (Cyperus rotundus L.) sobre o desenvolvimento inicial das plântulas desta alface. Os tratamentos experimentais foram constituídos de seis períodos crescentes e decrescentes de convivência, ou de controle das plantas daninhas na cultura, considerados a partir do plantio da alface; sendo separados em dois grupos: Mato e Limpo. No segundo experimento foram coletadas partes aéreas de tiririca, ocorrentes na área do experimento 1, que após secagem foram trituradas e imersas em álcool metílico P.A. nas proporções 10, 5,0 e 2,5% (p/v) e posteriormente impregnadas em papel de germinação, onde foram colocadas sementes de alface. Das análises dos resultados, conclui-se que a presença de plantas de C. rotundus pode interferir na germinação, crescimento e desenvolvimento das plantas de alface cv Lucy Brown, e que períodos iniciais de convivência entre a cultura e a daninha estão associados a uma indução do desenvolvimento de área foliar, e podem não expressar a redução de produtividade no final do ciclo. Períodos prolongados de competição induzem a redução da área foliar da alface, e consequentemente interferirão na produtividade dos campos.
Lettuce productivity cv Lucy Brown influenced by periods of coexisting with harmful plants and allelopathic potential of nutsedge
Keywords: Competition; Harmful plants; Lettuce